Optimisation of multi-stage production-inspection stations using genetic algorithm - Hassan, Azmi; Pham, Duc Trung (SIRIM, 2000)
The optimal allocation and sequencing of inspection stations is to be presented in this paper. The notion of optimality in this case encompasses factors such as the cost of inspection, the cost of allowing a defective unit to be output, and the cost of internal failure. The main goal of this work is to develop an efficient optimisation tool which will minimise the cost functions of the stated optimisation problems. The optimisation tool to be considered is Genetic Algorithm (GA). An introduction to the concepts of the GA and its encoding of the solutions to the problems in a genetic form and the evaluation of the resulting genetic code to give the fitness of those solutions will be discussed. The setting of the parameters for the genetic operators and the ways of initialising the solution population are also described. Finally, the results obtained are presented and compared to those produced by conventional methods.